2020
DOI: 10.7759/cureus.9244
|View full text |Cite
|
Sign up to set email alerts
|

Acute Psychosis Consequent to Total Thyroidectomy: An Etiological Conundrum

Abstract: Total thyroidectomy has evolved from a vilipended surgery owing to its high mortality to one with commonly performed surgery with minimal complications. After a total thyroidectomy many patients are left hypothyroid and/or hypoparathyroid, and thus prone to develop neuropsychiatric complications. Although anxiety and depression are the common manifestations, acute psychosis consequent to total thyroidectomy is rarely reported. Herein, we present the case of a 55-year-old female with a massive neck swelling dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Patients experiencing post-operative delirium from thyroidectomy are rare, limited to case reports. 18,25 Other documented complications from local literature include postoperative hemorrhage, and respiratory failure. 7 The local study of Villaluna and Desales showed that the histopathologic results of intrathoracic goiters were mostly multinodular adenomatous goiters (50%) and follicular adenomas (7%) 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients experiencing post-operative delirium from thyroidectomy are rare, limited to case reports. 18,25 Other documented complications from local literature include postoperative hemorrhage, and respiratory failure. 7 The local study of Villaluna and Desales showed that the histopathologic results of intrathoracic goiters were mostly multinodular adenomatous goiters (50%) and follicular adenomas (7%) 7 .…”
Section: Discussionmentioning
confidence: 99%